Meritve padavin med orografskim proženjem na območju Travljanske gore 8. septembra 2010 - Sinjur, Iztok (Gozdarski vestnik, 2011)
In the mountainous terrain precipitation amount could significantly vary locally. A study of an intense orographic precipitation event in the mountainous southern part of Slovenia was executed. The analysis was based on the data from an automatic weather station on the slope of Travljanska gora (876 m a., in the framework of the intensive forest monitoring programme) and some other official meteorological stations in surroundings. Hereby we verified the reliability of the automatic weather station's measurements. By comparing them with the data from official meteorological stations of the Environmental Agency of the Republic of Slovenia (ARSO) and Meteorological and Hydrological Service of Croatia (DHMZ), locality of orographic triggering was evidenced. Analyses proved significant local meteorological radar DSWR-88 reflectivity disturbances that originate in the specific weather situation and some disadvantages of this kind of remote sensing.
Keywords: orografske padavine; meteorološka postaja; gozdovi; Travljanska gora; Slovenia; Slovenija